Estudio de efectos ambientales y genéticos que influyen en la producción de leche y duración de lactación en bovinos de raza guzerat - Santos, Daniel Jordan de Abreu [UNESP]; Borquis, Rusbel Raúl Aspilcueta [UNESP]; Neto, Francisco Ribeiro de Araujo [UNESP]; Martins, Roberta Rollenberg Cabral [UNESP]; Jiménez, Enrique Acevedo; Manrique, Wilson Gomes [UNESP]; Tonhati, Humberto [UNESP] (My University, 2011)
Objective of present work was study a influence of environmental and genetic effects over characteristics of milk total production (PL) and lactation duration (DL), from 2572 lactations of 477 Guzerat cows, collected since 1957 to 2002, in Rio de Janeiro State. Environmental effects were analyzed by an statistical model that include male randomized effect, fixed effect of contemporary group, and the (co)variables age of cow (lineal and quadratic) and lactation duration. The contemporary group had significant effect just for PL. Bayesian inference was used to obtain estimatives of genetic parameters over an animal model, in which was included as fixed effect the contemporary group and the covariables age of cow (linear and quadratic). The estimates of heritability and repeatability were 0.36 and 0.75 for PL and 0.29 and 0.36 for DL, respectively. The estimated genetic correlation was 0.97. The heritability estimates for PL and DL were moderate, indicating that it is possible answer to the selection of the characteristics under study. The genetic correlation was high and indicates that selection for increase milk production will be accompanied with increase in lactation duration.
Study of environmental and genetic effects that influence milk production and duration of lactation in the Guzerat cattle breed
Keywords: Bayesian inference; Genetic parameters; Zebu cattle; Animalia; Bos; Bos indicus